(untitled) (NAU Journal of Library and Information Science, 2025)
This study examined institutional support as a possible predictor of librarians‟ attitude to consortium in university libraries in South-East, Nigeria. Three hypotheses were tested at 0.5 level of significance. The research design was a correlation. The population of the study comprised one hundred and seventy-one (171) librarians from the five federal university libraries in South- East Nigeria. Due to the manageable size of the population, total enumeration was used. Questionnaire was the instrument used for data collection. Data collected was analyzed using linear regressions and computed through Statistical Package for Social Sciences (SSPS, V20). The study found that institutional support, such as access to training and institutional infrastructure support, significantly predicts librarians‟ attitudes towards consortiums in university libraries in South-East Nigeria. However, results showed that institutional financial support does not significantly predict librarians‟ attitude towards consortium. The study concluded that access to training and institutional infrastructure support is key factor that can enhance librarians‟ attitude toward consortium. Based on the findings, the study recommends, among other things, that the University Management should prioritize adequate institutional support, conduct regular needs assessments to identify the training and development needs of librarians, and provide targeted support to enhance their participation in consortium.